Phytochemical properties and health benefits of pregelatinized Tartary buckwheat flour under different extrusion conditions - Zhang, Zhuo; Fan, Xin; Zou, Liang; Xing, Bao; Zhu, Manli; Yang, Xiushi; Ren, Guixing; Yao, Yang; Zhang, Lizhen; Qin, Peiyou (Frontiers in Nutrition, 2022)
This work investigated the phytochemical properties and health benefits of Tartary buckwheat flour obtained with different extrusion conditions including high, medium, and low temperature. Extrusion significantly decreased the fat content and changed the original color of Tartary buckwheat flour. The contents of protein, total flavonoids and D-chiro-inositol were affected by the extrusion temperature and moisture. Extrusion significantly decreased the total flavonoids and flavonoid glycosides contents, while it significantly increased aglycones. Compared to native Tartary buckwheat flour and pregelatinization Tartary buckwheat flour obtained with high temperature, the pregelatinization Tartary buckwheat flour obtained by medium and low temperature contained higher aglycones and lower flavonoid glycosides, which had stronger antioxidant capacity, α-glucosidase inhibitory activity and relatively mild α-amylase inhibitory activity. Correlation analysis proved that the aglycone content was positively correlated with antioxidant and α-glucosidase inhibitory activities. These findings indicate that the pregelatinization Tartary buckwheat flour obtained by medium and low temperature could be used as an ideal functional food resource with antioxidant and anti-diabetic potential.